(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Fashion serves as a powerful tool for cultural expression, reflecting historical traditions, social identity, and artistic creativity. In an era of globalization, where fashion trends rapidly evolve and often favor Westernized styles, preserving national identity in fashion has become an essential cultural and economic objective. This thesis explores the importance of maintaining and popularizing national identity in fashion, with a particular focus on traditional Uzbek clothing, fabrics, and handicrafts. By integrating historical textile techniques, embroidery, and symbolic patterns into contemporary fashion, nations can safeguard their cultural heritage while appealing to modern global audiences. The paper also examines strategies for promoting national identity in fashion through education, media, and international collaborations.